2002
DOI: 10.1001/archpedi.156.11.1129
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Outcome Following Third Trimester Exposure to Paroxetine

Abstract: When used near term, paroxetine is associated with a high rate of neonatal complications, possibly caused by its common discontinuation syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
182
3
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 238 publications
(194 citation statements)
references
References 10 publications
6
182
3
3
Order By: Relevance
“…Data on neonatal outcomes at birth were obtained from the neonatal health records including gestational age at birth, birth weight, length, head circumference, Apgar scores at 1 and 5 min, and whether the infant exhibited symptoms of postnatal adaptation syndrome-a cluster of symptoms reported in ~30% of neonates exposed to SRIs in utero (28) including rapid breathing, respiratory distress, jitteriness, and abnormal tone (29)(30)(31)(32).…”
Section: Maternal Characteristics and Neonatal Datamentioning
confidence: 99%
“…Data on neonatal outcomes at birth were obtained from the neonatal health records including gestational age at birth, birth weight, length, head circumference, Apgar scores at 1 and 5 min, and whether the infant exhibited symptoms of postnatal adaptation syndrome-a cluster of symptoms reported in ~30% of neonates exposed to SRIs in utero (28) including rapid breathing, respiratory distress, jitteriness, and abnormal tone (29)(30)(31)(32).…”
Section: Maternal Characteristics and Neonatal Datamentioning
confidence: 99%
“…Children exposed to SSRIs in utero have been followed for up to 72 months postnatally and have not been reported to display increased behavioral abnormalities compared to unexposed children although they have been reported to display subtle changes in motor development and in motor movement control (Costei et al, 2002;Nulman et al, 2002;Casper et al, 2003). However, no study has followed such children beyond early childhood.…”
Section: Introductionmentioning
confidence: 99%
“…1 Some studies report that third trimester exposure leads to reduced Apgar scores 2 and low birth weight, as well as increased rates of premature birth and increased risk for admission to special care nurseries, 3 while other studies have not found similar outcomes. 4,5 Concern about these adverse outcomes led the US FDA 6 (US Food and Drug Administration) and Health Canada 7 to issue warnings in 2004 regarding late pregnancy use of SRIs. Compounding medication-related effects, adverse neonatal behaviors have also been observed following exposure to maternal depression alone 8 and therefore identifying SRI-related outcomes has been challenged by the difficulty of distinguishing medication effects from the effects of the maternal disease itself.…”
Section: Introductionmentioning
confidence: 99%